TAFSĪR TAHLĪLĪ (INTERPRETASI ANALITIS) QS. AL-FURQĀN [25]: 1-11 - Kholik Ramdan Mahesa (IAIN Madura, 2021)
This paper examines the various interpretations of the tafsir scholars of surah al-Furqān. In the study of tafseer ('ulūm al-Qur'ān) there are several methods or ways of examining the contents of the al-Qur'an such as the Ijmali, Tahlīlī, Mauḍu'ī and muqaran methods. This study is focused on the interpretation of the tafsir scholars of surah al-Furqān [25]: 1-11 with the Tahlīlī Tafsir method approach. The author uses a literature study (Library Research) so that he finds findings on the interpretation of surah al-Furqān that the content in surah al-Furqān explains about monotheism towards Allah and Allah hates those who associate him (infidels). Keyword: Tafseer Tahlīlī, interpretations, Surah al-Furqān